Leaf venation of Lauraceae species (excluding Ocotea) from the Reserva Natural Vale, Linhares, Espírito Santo, Brazil - de Moraes, Pedro Luís Rodrigues [UNESP]; da Cruz, Isabel Cristina Lima [UNESP]; Coan, Alessandra Ike [UNESP]; Tomazello Filho, Mario (Wiley, 2021)
With the aim of recognizing and identifying both fertile and sterile specimens of Lauraceae from the Reserva Natural Vale, Linhares, we analyzed the leaf venation pattern of 20 species belonging to 11 genera. The venation patterns of 12 species are described and illustrated for the first time here. A dichotomous identification key was built from a matrix of 12 venation characters with 38 states, which allowes to distinguish the taxa.
Keywords: Laurales; leaf venation; morphology; Neotropics; taxonomy